Propuesta de mejoramiento continuo para incrementar la efectividad en el área de operaciones de la empresa sakura s.a. - Castillo Jaurégui, Alan Daniel (2016)
This research determined how the implementation of the methodology of continuous improvement increases the effectiveness of the area of operations of the company Transportation Sakura S.A. The Continuous Improvement is a Japanese methodology, whose philosophy focuses on constantly improving organizations with the Deming cycle: Acting, Planning Do & Check. And the effectiveness referenced throughout the investigation is defined as the achievement of results scheduled in time and with the best possible reasonable costs, is doing the right thing with great accuracy and without any waste of time or money. The population are the effectiveness of the area of operations of the company Sakura S.A. and shows the effectiveness of the area of operations of the company Sakura S.A. 2015. The sampling is not probabilistic for convenience. The research design is the pre experimental with pretest and posttest. The technique for collecting data was library research, interviews, meetings and documentary research. The implementation of the methodology of continuous improvement in the area of operations of the company Sakura S.A., greatly enhanced the effectiveness of the area of operations of the company Sakura S.A warehouse, from 1.51 in the year 2015 to 1.71 in 2016.